2021
DOI: 10.1186/s12885-021-08086-y
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP2 acts as an independent prognostic factor and is related to immunosuppression in DLBCL

Abstract: Background Almost one-third of patients with diffuse large B-cell lymphoma (DLBCL) cannot be cured with initial therapy and will eventually succumb to the disease. Further elaboration of prognostic markers of DLBCL will provide therapeutic targets. IQ motif-containing GTPase activating protein 2 (IQGAP2) acts as a tumour suppressor in hepatocellular, prostate, and gastric cancers. However, the role of IQGAP2 in DLBCL remains unclear. Methods We col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Our results also indicated that a low level of total protein is associated with genetic liability to female depression including PND. Fine-grained local genetic correlation analysis implicated IQGAP2, for which increased expression has been associated with immunosuppression and poor prognosis in lymphoma [69] but improved prognosis in breast cancer [70]. Nominally significant local negative genetic correlation for total protein with female depression was found for the 5p15.33 genomic region, which contains TERT, associated with the length of telomeres and associated genomic stability [71].…”
Section: Discussionmentioning
confidence: 99%
“…Our results also indicated that a low level of total protein is associated with genetic liability to female depression including PND. Fine-grained local genetic correlation analysis implicated IQGAP2, for which increased expression has been associated with immunosuppression and poor prognosis in lymphoma [69] but improved prognosis in breast cancer [70]. Nominally significant local negative genetic correlation for total protein with female depression was found for the 5p15.33 genomic region, which contains TERT, associated with the length of telomeres and associated genomic stability [71].…”
Section: Discussionmentioning
confidence: 99%
“…IQGAP2 has been reported as a tumor suppressor in hepatocellular cancer, prostate cancer, and gastric cancer [ 35 ]. However, IQGAP2 is a negative prognostic factor and is associated with immunosuppression in diffuse large B-cell lymphoma [ 36 ]. IQGAP2 was defined as a risk-conferring gene in this study and its role in LGG needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Higher CCND2 expression is associated with more efficient R-CHOP treatment and better prognosis of ABC-DLBCL [ 20 ]. High IQGAP2 level predicted shorter OS of DLBCL and was positively related to immunosuppressive gene expression in DLBCL [ 21 ]. The current investigation used TCGA database and uncovered the dysregulation of ACTR2 in 14 types of human cancer tissues in addition to DLBCL, suggesting its potential importance in cancer progression.…”
Section: Discussionmentioning
confidence: 99%